Dapsone as first line therapy for bullous pemphigoid. - Venning, V; Millard, P; Wojnarowska, F (1989)
In an open study, a total of 18 patients with proven bullous pemphigoid (16 new patients and two in relapse) were treated with a trial of dapsone (17 patients) or sulphonimide (one patient). Overall, eight patients were controlled on one of these agents as the sole treatment (44%). Six patients had a partial, but inadequate response, while four did not respond. The responses to the sulpha drugs were generally rapid, i.e. within 2 weeks, and the maximum doses used in any patient were 100 mg/day dapsone and 1.5 g/day of sulphapyridine or sulphamethoxypyridazine. Significant side-effects to dapsone occurred in six of the 17 patients. A trial of a sulphone or sulphonamide drug is warranted in bullous pemphigoid both as an initial treatment or in the treatment of relapse, particularly when there is a contraindication to the use of corticosteroids. Side-effects are common and therapy needs to be closely monitored.